Efficient Parking Management Using the IoT Technology - Rathore, Ayushi; Anjali; Abdul Qadeer, Mohammed (International Journal of Computer Sciences and Engineering, 2025)
Parking management in the populous country like India is very arduous. Most of the time, finding a parking lot with vacant spaces is a critical task which requires a lot of time and efforts to be made. Thus, after analysing the problem closely, we came up with a system that can effectively solve the problem of parking in metro/big cities using the IoT technology. The IoT architecture, in turn, will efficiently handle the parking space & overcome the problem of traffic caused by irregular parking on the roadsides, thus, managing time of the people. The architecture uses small-sized ultrasonic sensor which sizes about a bottle cap slotted with a wireless sensor node to send data to the Raspberry Pi, which further process the collected data and send it to the cloud. A Web App/Android App will measure the distance between user’s current location & nearby parking lots within the specified distance range using Haversian algorithm that works along the earth’s radius. The system also allows the user to reserve a parking space for a duration of time in advance.